Reduction of False Convictions through Improved Identification Procedures: Further Refinements for Street Practice and Public Policy, 1983-2010, in five countries - Steblay, Nancy ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study was a three part project which evaluated the procedural aspects of police lineups. The first part was a meta-analysis of existing laboratory data on comparative eyewitness accuracy rates for sequential versus simultaneous lineups. The second part was three experiments on the elements of current field lineup practices in simultaneous and sequential lineups. The third part was a field experiment in Tucson, Arizona, which tested double-blind simultaneous versus double-blind sequential lineups.